Head-to-head randomized trials are mostly industry sponsored and almost always favor the industry sponsor - Flacco, Maria Elena; Manzoli, Lamberto; Boccia, Stefania; Capasso, Lorenzo; Aleksovska, Katina; Rosso, Annalisa; Scaioli, Giacomo; De Vito, Corrado; Siliquini, Roberta; Villari, Paolo; Ioannidis, John P.A. (Journal of clinical epidemiology, 2015)
To map the current status of head-to-head comparative randomized evidence and to assess whether funding may impact on trial design and results. From a 50% random sample of the randomized controlled trials (RCTs) published in journals indexed in PubMed during 2011, we selected the trials with ≥100 participants, evaluating the efficacy and safety of drugs, biologics, and medical devices through a head-to-head comparison. We analyzed 319 trials. Overall, 238,386 of the 289,718 randomized subjects (82.3%) were included in the 182 trials funded by companies. Of the 182 industry-sponsored trials, only 23 had two industry sponsors and only three involved truly antagonistic comparisons. Industry-sponsored trials were larger, more commonly registered, used more frequently noninferiority/equivalence designs, had higher citation impact, and were more likely to have “favorable” results (superiority or noninferiority/equivalence for the experimental treatment) than nonindustry-sponsored trials. Industry funding [odds ratio (OR) 2.8; 95% confidence interval (CI): 1.6, 4.7] and noninferiority/equivalence designs (OR 3.2; 95% CI: 1.5, 6.6), but not sample size, were strongly associated with “favorable” findings. Fifty-five of the 57 (96.5%) industry-funded noninferiority/equivalence trials got desirable “favorable” results. The literature of head-to-head RCTs is dominated by the industry. Industry-sponsored comparative assessments systematically yield favorable results for the sponsors, even more so when noninferiority designs are involved.